Determining the uniformity and consistency of droplet size across spray drift reducing nozzles in a wind tunnel. (October 2015) - Ferguson, J. Connor; O'Donnell, Chris C.; Chauhan, Bhagirath S.; Adkins, Steve W.; Kruger, Greg R.; Wang, Ruobing; Urach Ferreira, Pedro H.; Hewitt, Andrew J.
Abstract: Spray drift is a consideration for growers and applicators who are increasingly selecting larger droplet producing nozzles to allay their concerns. As new technologies arrive on the market, the prices of individual nozzles have risen which puts a greater need for consistency among nozzles to be worth the investment. These nozzles, while effective at reducing spray drift, may not always be consistent at maintaining efficacy which can be a result of a lack of uniformity in the production of these nozzles. Twenty-one spray drift reducing nozzles were compared for droplet size distributions across three liquids of varying dynamic surface tensions in a wind tunnel at the University of Queensland. Research sought to identify the repeatability of each nozzle type by randomly selecting five units to test consistency of droplet size measurements across nozzle type. Results indicate that some nozzle types are consistent and repeatable while others are not. It was also observed that some nozzle types are relatively unaffected by liquid type, where others resulted in a droplet size change in volume median diameter (VMD) of 100 μm depending on liquid type at the same operating pressure. Research from this study will help growers and industry to select the best nozzle types to ensure uniformity of application, to maximize efficacy and to reduce pesticide spray drift. Highlights: Nozzle type uniformity testing resulted in CVs ranging from 0.5% to 7.6%. 75% of all nozzle types tested had CV values below 4%. Spray solution was a source of variation in droplet size for 25% of nozzle types. Water alone resulted in the greatest differences in consistency. Not all drift reducing nozzles are created equal.